Mutational analysis of putative phosphate- and proton-binding sites in the Saccharomyces cerevisiae Pho84 phosphate:H(+) transceptor and its effect on signalling to the PKA and PHO pathways - Samyn, Dieter R; Ruiz-Pávon, Lorena; Andersson, Michael R; Popova, Yulia; Thevelein, Johan M; Persson, Bengt L (Biochemical journal, 2012)
In Saccharomyces cerevisiae, the Pho84 phosphate transporter acts as the main provider of phosphate to the cell using a proton symport mechanism, but also mediates rapid activation of the PKA (protein kinase A) pathway. These two features led to recognition of Pho84 as a transceptor. Although the physiological role of Pho84 has been studied in depth, the mechanisms underlying the transport and sensor functions are unclear. To obtain more insight into the structure-function relationships of Pho84, we have rationally designed and analysed site-directed mutants. Using a three-dimensional model of Pho84 created on the basis of the GlpT permease, complemented with multiple sequence alignments, we selected Arg(168) and Lys(492), and Asp(178), Asp(358) and Glu(473) as residues potentially involved in phosphate or proton binding respectively, during transport. We found that Asp(358) (helix 7) and Lys(492) (helix 11) are critical for the transport function, and might be part of the putative substrate-binding pocket of Pho84. Moreover, we show that alleles mutated in the putative proton-binding site Asp(358) are still capable of strongly activating PKA pathway targets, despite their severely reduced transport activity. This indicates that signalling does not require transport and suggests that mutagenesis of amino acid residues involved in binding of the co-transported ion may constitute a promising general approach to separate the transport and signalling functions in transceptors.